2017
DOI: 10.1007/s00784-016-2043-5
|View full text |Cite
|
Sign up to set email alerts
|

In situ effect of enamel salivary exposure time and type of intraoral appliance before an erosive challenge

Abstract: This finding will help researchers in the development of erosion studies, which will provide information for dentists to offer a better treatment for erosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 54 publications
2
28
0
8
Order By: Relevance
“…Thus, it is possible that for the AEP challenged with intrinsic acid (HCl), a long time of maturation is important for the protection against demineralization. In line with this hypothesis, an in situ study showed that exposure to saliva for 30 min for AEP formation promoted less enamel resistance to HCl erosive attack than exposure to saliva for 2 h [Mendonça et al, 2017]. This suggests that more mature pellicles might provide higher protection against intrinsic erosion than short-term pellicles.…”
Section: And Itsupporting
confidence: 54%
“…Thus, it is possible that for the AEP challenged with intrinsic acid (HCl), a long time of maturation is important for the protection against demineralization. In line with this hypothesis, an in situ study showed that exposure to saliva for 30 min for AEP formation promoted less enamel resistance to HCl erosive attack than exposure to saliva for 2 h [Mendonça et al, 2017]. This suggests that more mature pellicles might provide higher protection against intrinsic erosion than short-term pellicles.…”
Section: And Itsupporting
confidence: 54%
“…Initial erosion lesions were induced by hydrochloric acid exposure, which has been used in several in situ studies [9,23,25,26] to simulate the acidity of the gastric juice, often an intrinsic cause for the development of dental erosion [27]. The erosive challenge was performed ex vivo due to ethical restrictions and to guarantee greater control and standardization of the demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…The intraoral palatal appliances were made with acrylic resin on a plaster model of the upper arch of each volunteer; a new appliance was made for each phase of the study [21,23]. Acrylic appliances had two vertical rows, one on the right and the other on the left side, with one cavity (12 × 6 × 3 mm) for the fixation of two blocks.…”
Section: Volunteers and In Situ Experimentsmentioning
confidence: 99%
See 2 more Smart Citations